Criteria for Supplier Selection: An Application of AHP-SCOR Integrated Model (ASIM) - Nazim, Raja; Raja Yaacob, Raja Ahmad Iskandar (International Journal of Supply Chain Management, 2017)
Supplier selection has become one important facet in supply chain management. As many conflicting aspects to take into account, supply chain performance is spectacularly elevated due to the enhancement of supplier selection problem in many areas. This paper introduces the new methodology based on integration of analytical hierarchy process. Questionnaire was sent to all stand-alone largest hypermarkets in Selangor, Malaysia to correlate the precedence importance based on 41 criteria in selecting the suppliers. The survey highlights the results that intensify the use of integration of AHP-SCOR model in assisting decision maker to effectively evaluate numerous suppliers. The results amplify the most appropriate decision making method providing the implication of newness development of integrated model.